ICP27 Interacts with the RNA Export Factor Aly/REF To Direct Herpes Simplex Virus Type 1 Intronless mRNAs to the TAP Export Pathway - Chen, I-Hsiung Brandon (American Society for Microbiology, 2002)
Herpes simplex virus type 1 (HSV-1) protein ICP27 facilitates the export of viral intronless mRNAs. ICP27 shuttles between the nucleus and cytoplasm, which has been shown to require a leucine-rich nuclear export sequence (NES). ICP27 export was reported to be sensitive to the CRM1 inhibitor leptomycin B (LMB) in HSV-1-infected cells but not in Xenopus oocytes, where ICP27 interacts with the export factor Aly/REF to access the TAP export pathway. Here, we show that ICP27 interacts with Aly/REF in HSV-1-infected mammalian cells and that Aly/REF stimulates export of viral intronless RNAs but does not cross-link to these RNAs. During infection, Aly/REF was no longer associated with splicing factor SC35 but moved into structures that colocalized with ICP27, suggesting that ICP27 recruits Aly/REF from spliceosomes to viral intronless RNAs. Further, ICP27 was found to interact in vivo with TAP but not with CRM1. In vitro export assays showed that ICP27 export was not sensitive to LMB but was blocked by a dominant-negative TAP deletion mutant lacking the nucleoporin interaction domain. These data suggest that ICP27 uses the TAP pathway to export viral RNAs. Interestingly, the leucine-rich N-terminal sequence was required for efficient export, even though ICP27 export was LMB insensitive. Thus, this region is required for efficient ICP27 export but does not function as a CRM1-dependent NES.